2018
DOI: 10.1016/j.ejvs.2017.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Editor's Choice – An Updated Systematic Review and Meta-analysis of Outcomes Following Eversion vs. Conventional Carotid Endarterectomy in Randomised Controlled Trials and Observational Studies

Abstract: Using combined RCT and OS data, eCEA was superior to cCEA regarding peri-operative outcomes (stroke, death, death/stroke) and late restenosis, but was similar to patched CEA in both early and late outcomes. This updated meta-analysis suggests that early and late outcomes following cCEA are similar to eCEA, provided the arteriotomy is patched.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 33 publications
0
22
1
1
Order By: Relevance
“…It was documented that eversion technique improves perioperative stroke and death rates compared with the conventional method and less restenosis is achieved in the late period. However, it is also stated that similar results were obtained with the conventional method modified using a patch [18,19]. Routine shunt use during surgery does not provide superiority in terms of stroke and mortality compared to not using it at all.…”
Section: Discussionmentioning
confidence: 77%
“…It was documented that eversion technique improves perioperative stroke and death rates compared with the conventional method and less restenosis is achieved in the late period. However, it is also stated that similar results were obtained with the conventional method modified using a patch [18,19]. Routine shunt use during surgery does not provide superiority in terms of stroke and mortality compared to not using it at all.…”
Section: Discussionmentioning
confidence: 77%
“…For these patients, endarterectomies can reduce their 5-year risk of stroke occurrence from 12 to 6% (126). Recent studies have found that a modified version of this surgery, eversion carotid endarterectomy, might have better peri-operative outcomes but performs similarly for post-operative outcomes (127).…”
Section: Variation In Disease Prediction and Treatmentmentioning
confidence: 99%
“…Previous reviews such as the one by Paraskevasa et al 32 could be considered as ‘similar’ to this review. However, the differences can be found in the methodological approach.…”
Section: Introductionmentioning
confidence: 79%